Arx expansion mutation perturbs cortical development by augmenting apoptosis without activating innate immunity in a mouse model of X-linked infantile spasms syndrome - Meagan S. Siehr; Cory A. Massey; Jeffrey L. Noebels (The Company of Biologists, 2020)
X-linked infantile spasms syndrome (ISSX) is a clinically devastating developmental epileptic encephalopathy with life-long impact. Arx(GCG)10+7, a mouse model of the most common triplet-repeat expansion mutation of ARX, exhibits neonatal spasms, electrographic phenotypes and abnormal migration of GABAergic interneuron subtypes. Neonatal presymptomatic treatment with 17β-estradiol (E2) in Arx(GCG)10+7 reduces spasms and modifies progression of epilepsy. Cortical pathology during this period, a crucial point for clinical intervention in ISSX, has largely been unexplored, and the pathogenic cellular defects that are targeted by early interventions are unknown. In the first postnatal week, we identified a transient wave of elevated apoptosis in Arx(GCG)10+7 mouse cortex that is non-Arx cell autonomous, since mutant Arx-immunoreactive (Arx+) cells are not preferentially impacted by cell death. NeuN+ (also known as Rbfox3) survival was also not impacted, suggesting a vulnerable subpopulation in the immature Arx(GCG)10+7 cortex. Inflammatory processes during this period might explain this transient elevation in apoptosis; however, transcriptomic and immunohistochemical profiling of several markers of inflammation revealed no innate immune activation in Arx(GCG)10+7 cortex. Neither neonatal E2 hormone therapy, nor ACTH(1-24), the frontline clinical therapy for ISSX, diminished the augmented apoptosis in Arx(GCG)10+7, but both rescued neocortical Arx+ cell density. Since early E2 treatment effectively prevents seizures in this model, enhanced apoptosis does not solely account for the seizure phenotype, but may contribute to other aberrant brain function in ISSX. However, since both hormone therapies, E2 and ACTH(1-24), elevate the density of cortical Arx+-interneurons, their early therapeutic role in other neurological disorders hallmarked by interneuronopathy should be explored. This article has an associated First Person interview with the first author of the paper.